A useful empirical bayesian method to analyse industrial data from saturated factorial designs - Yukie Baba, Marta [UNESP]; Alberto Achcar, Jorge [UNESP]; Antonio Moala, Fernando [UNESP]; Minoru Oikawa, Sergio [UNESP]; Luis Piratelli, Claudio (Growing Science, 2013)
The use of saturated two-level designs is very popular, especially in industrial applications where the cost of experiments is too high. Standard classical approaches are not appropriate to analyze data from saturated designs, since we could only get the estimates of the main factor effects and we would not have degrees of freedom to estimate the variance of the error. In this paper, we propose the use of empirical Bayesian procedures to get inferences for data obtained from saturated designs. The proposed methodology is illustrated assuming a simulated data set. © 2013 Growing Science Ltd. All rights reserved.
Keywords: Empirical bayesian methods; Plackett-burman designs; Saturated designs